A contractor's guide to planning, scheduling, and control - Holm, Len (Wiley Professional Development, 2022)
Construction project management fundamentals such as preconstruction planning, scheduling, project management, and construction management controls are widely taught in nearly every 4-year and 2-year construction management and construction engineering program in the US. The success of a construction project is almost entirely dependent on a well-defined schedule that allows for the inevitable delay or unexpected change. Schedulers manage everything from staffing requirements, material deliveries and inspections, equipment needs, etc., all of which calls for a thorough understanding of the construction process and workflow.